Analysis of magneto-optical properties for three-dimensional photonic crystals in high-symmetry arrangement doped by metamaterials and uniaxial materials. (November 2016) - Yu, Bing; Li, Heming; Wang, Shenyun; Wan, Fayu; Ge, Junxiang
Abstract: In this paper, we use a modified plane wave expansion (PWE) method to investigate the properties of photonic band gaps (PBGs) for the extraordinary mode in the three-dimensional (3D) photonic crystals (PCs) which are composed of the anisotropic dielectric (the uniaxial materials) spheres immersed in the homogeneous metamaterials (epsilon-negative materials) background with high-symmetry (body-centered-cubic) lattices, as the magneto-optical Voigt effects are considered. The equations for calculating the PBGs in the first irreducible Brillouin zone are theoretically derived. It is numerically illustrated that the anisotropic PBGs and two flattened band regions can be achieved. The influences of the ordinary-refractive index, extraordinary-refractive index, filling factor of dielectric spheres, electronic plasma frequency and cyclotron frequency on the magneto-optical properties of such 3D PCs also are studied in detail, respectively, and some corresponding physical explanations are given. The numerical results demonstrate that the anisotropy can open partial band gaps in the proposed PCs, and the complete PBGs can be obtained compared with the conventional PCs only containing the isotropic material with similar structures. The bandwidths of PBGs can be tuned by introducing the epsilon-negative materials into such PCs containing the uniaxial materials. The anisotropic PBGs can be manipulated by the parameters as mentioned above. As the proposed PCs with high-symmetry lattices, the complete PBGs can be obtained by introducing the uniaxial materials. Highlights: The equations for computing the PBGs are deduced. The introduced uniaxial materials can enhance the PBG. The PBGs can be tuned by f, n e, n o, ω c and ω p, respectively. γ has no effect on the PBGs.